2018
DOI: 10.1038/s41598-018-35495-0
|View full text |Cite
|
Sign up to set email alerts
|

Interplay among steroids, body condition and immunity in response to long-term captivity in toads

Abstract: Stressful experiences can promote harmful effects on physiology and fitness. However, stress-mediated hormonal and immune changes are complex and may be highly dependent on body condition. Here, we investigated captivity-associated stress effects, over 7, 30, 60, and 90 days on plasma corticosterone (CORT) and testosterone (T) levels, body index, and innate immunity (bacterial killing ability and phagocytosis of peritoneal cells) in toads (Rhinella icterica). Toads in captivity exhibited elevated CORT and decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
0
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 73 publications
1
51
0
3
Order By: Relevance
“…Meanwhile, for the individuals in the field displaying high baseline CORT, we observed a tendency to decrease CORT plasma levels following 24h restraint. These toads were already displaying high CORT in the field probably due to reproductive behavior (calling activity) [27], precluding the assessment of increased CORT values 24h post-restraint [11]. Moreover, the trend to decreased CORT 24h post-restraint in these toads also corroborates the observation that the peak of GC release in response to restraint occurs before 24h of exposure to this stressor.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…Meanwhile, for the individuals in the field displaying high baseline CORT, we observed a tendency to decrease CORT plasma levels following 24h restraint. These toads were already displaying high CORT in the field probably due to reproductive behavior (calling activity) [27], precluding the assessment of increased CORT values 24h post-restraint [11]. Moreover, the trend to decreased CORT 24h post-restraint in these toads also corroborates the observation that the peak of GC release in response to restraint occurs before 24h of exposure to this stressor.…”
Section: Discussionsupporting
confidence: 53%
“…Toads displaying high CORT levels in the field (those exhibiting calling behavior at the moment of capture [27]) showed a tendency to decrease CORT after restraint for 24h (S1 Table, P = 0.082, Fig 1A). Meanwhile, toads characterized by low CORT levels at time 0h (before initiating restraint) showed increased CORT plasma levels after 1 and 24h post-restraint (S1 Table, P = 0.003, Fig 1B).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To evaluate R. ornata individuals' health, we assessed morphological and physiological traits generally used as indicators of physiological condition and exposure to contaminants: individuals' body condition, proportional organ masses and white blood cell counts. Body condition, which ultimately expresses the mass-to-length relationship, is widely used as an indicator of individual nutritional condition and has been shown to be positively correlated with fecundity (Reading and Clarke, 1995), individual fitness (Jakob, Marshall, and Uetz, 1996) and habitat quality (Janin, Léna, and Joly, 2011), and negatively associated with chronic stress response (Titon et al, 2017). In turn, proportional increases in liver and kidneys masses have been shown to reflect increased detoxification function (e. g. Arrieta et al, 2004), whereas proportional 6 decrease in gonads has been shown to indicate reduced fertility (e. g. Rie et al, 2005).…”
Section: Introductionmentioning
confidence: 99%